Discovery of the bacterial HslV protease activators as lead molecules with novel mode of action - Aurangzeb Sana; Aurongzeb Muhammad; Shamim Shahbaz; Rashid Yasmeen; Khan Khalid Mohammed; Aziz Tariq; Alharbi Metab; Alasmari Abdullah F. (Open Chemistry)
The HslVU enzyme complex, a proteasomal analog found in bacteria, consists of two components, i.e., the HslV protease and the HslU ATPase. These proteins come together to form a functional enzyme complex, where the C-terminal helix of each HslU subunit is inserted into the binding pocket of each HslV dimer. This interaction leads to the activation of the HslV protease through allosteric mechanisms, enabling its enzymatic function. This bacterial complex is reflected as an attractive target for drug development due to its presence in disease-causing microorganisms and concurrent absence in humans. The objective of this research was to identify certain promising drug candidates that could excessively stimulate the HslV protease, leading to uncontrolled protein breakdown in the pathogens. Four dihydropyrimidone derivatives have been identified as potential activators of HslV protease exhibiting high docking scores, favorable binding patterns, and significant in vitro activation capabilities. These compounds have demonstrated effective dose 50 values within the sub-micromolar range, i.e., 0.4–0.58 µM. Normal mode analysis investigations provided additional confirmation regarding the stability of the conformational interactions between the HslV protease and the active compounds. In addition, the predicted absorption, distribution, metabolism, excretion, and toxicity properties of these lead compounds remarkably demonstrated their considerable drug-like and non-toxic qualities. This study not only presents more potent small non-peptide activators of the HslV protease but also enhances the understanding regarding the mechanism of HslVU complex activation via small non-peptidic molecules.